An Optimized Metagenomic Approach for Virome Detection of Clinical Pharyngeal Samples With Respiratory Infection - Liu, Bo; Shao, Nan; Wang, Jing; Zhou, SiYu; Su, HaoXiang; Dong, Jie; Sun, LiLian; Li, Li; Zhang, Ting; Yang, Fan (Frontiers in Microbiology, 2020)
Respiratory virus infections are one of the major causes of acute respiratory disease or exacerbation of chronic obstructive pulmonary disease (COPD). However, next-generation sequencing has not been used for routine viral detection in clinical respiratory samples owing to its sophisticated technology. Here, several pharyngeal samples with COPD were collected to enrich viral particles using an optimized method (M3), which involved M1 with centrifugation, filtration, and concentration, M2 (magnetic beads) combined with mixed nuclease digestion, and M4 with no pretreatment as a control. Metagenomic sequencing and bioinformatics analyses showed that the M3 method for viral enrichment was superior in both viral sequencing composition and viral taxa when compared to M1, M2, and M4. M3 acquired the most viral reads and more complete sequences within 15-h performance, indicating that it might be feasible for viral detection in multiple respiratory samples in clinical practice. Based on sequence similarity analysis, 12 human viruses, including nine Anelloviruses and three coronaviruses, were characterized. Coronavirus OC43 with the largest number of viral reads accounted for nearly complete (99.8%) genome sequences, indicating that it may be a major viral pathogen involved in exacerbation of COPD.